Species diversity at 5 schools in Kuching city, Kota Samarahan, and Serian town, Sarawak - Muhammad Thoiyib, Noor Zainy (Universiti Malaysia Sarawak (UNIMAS), 2015)
8357 individual trees and shrubs were enumerated from five schools composing of 128 species. The highest species diversity Index of tree population was recorded at SMK Kota Samarahan with 11.9, followed by SMK Serian with 9.1 and SMK Wira Penrissen with Species Diversity Index (SDI) of 8.92. SMK Gedong the Species Diversity Index with 8.5, while SMK Tungku Abdul Rahman has the lowest Species Diversity with 6.2. The health conditions of the plant species in terms of maintenance aspects were also discussed. The data obtained will be useful for managers to have wide background of urban trees.